From Perugino to Picasso revisited: Electrophysiological responses to faces in paintings from different art styles - Ventura, Paulo (2024)
Behavioral research (Ventura, et al., 2023) suggested that pictorial representations of faces varying along a realism-distortion spectrum elicit holistic processing as natural faces. Whether holistic face neural responses are engaged similarly remains, however, underexplored. In the present study, we evaluated the neural correlates of naturalist and artistic face processing, by exploring electrophysiological responses to faces in photographs versus in four major painting styles. The N170 response to faces in photographs was indistinguishable from that elicited by faces in the renaissance art style (depicting the most realistic faces), whilst both categories elicited larger N170 than faces in other art styles (post-impressionism, expressionism, and cubism), with a gradation in brain activity. The present evidence suggest that visual processing may become finer grained the more the realistic nature of the face. Despite behavioral equivalence, the neural mechanisms for holistic processing of natural faces and faces in diverse art styles are not equivalent.